MODELING OF CALCITE DISSOLUTION BY OXIC RESPIRATION IN SUPRALYSOCLINAL DEEP-SEA SEDIMENTS - Adler M.; Hensen C.; Wenzhofer F.; Pfeifer K.; Schulz H.D. (My University, 2001)
Pore-water profiles of CO2, pH, Ca2+ and O2 in situ concentrations were measured at two stations on the upper continental slope off Gabon. The present study evaluates these measurements concerning their implications for the calcium carbonate system in deep-sea sediments. The model CoTReM, which was used to simulate the dynamics of this complex geochemical system, revealed a strong dependence of calcite dissolution on oxic respiration at both sites. All simulated calcite dissolution kinetics reached a dynamic equilibrium with almost equal calcite dissolution rates, but different sub-saturation states and pH values. The latter are mainly dependent on boundary conditions and kinetic rate law parameters. Boundary conditions are of immense importance. They define which pH deviations between measured data and the simulated equilibration (instantaneous kinetics) have still to be fitted by kinetic restrictions per rate law for the equilibration. These pH deviations set up the range of possible values for rate constants in a given rate law to yield a well simulated pH. A failure in the implementation of these boundary conditions may lead to non-linearly flawed rate constants, which fit only one (usually the maximal) pH deviation well. The whole depth distribution of pH deviations has to be fitted very well by a kinetic rate law. Only this procedure secures that the used boundary conditions and rate laws/constants are acceptable. Nevertheless, several kinetic rate laws may be used for good pH fits, featuring clear differences in parameter values for rate constants and reaction orders. The connection between these rate laws with different parameters is examined and the dependence of the rate constant on the given form of the rate law is demonstrated. This study achieves rate constants of 0.038 and 18%/d for a dissolution rate law of 4.5th reaction order and sub-saturation dependence from the term (1-Ω). These results are well within the range of rate constants obtained during former field studies for the same form of the dissolution rate law.
Keywords: CALCITE; DISSOLUTION KINETICS; NUMERICAL MODEL; OPERATOR-SPLITTING; PHREEQC